GlideScope Cobalt Videolaryngoscope. (February 2015) - Fiadjoe, John E.; Isserman, Rebecca S.; Gurnaney, Harshad; Kovatsis, Pete G.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.